2007
DOI: 10.2353/ajpath.2007.061116
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Glomerular Basement Membrane Charge through Podocyte-Specific Mutation of Agrin Does Not Alter Glomerular Permselectivity

Abstract: Glomerular charge selectivity has been attributed to anionic heparan sulfate proteoglycans (HSPGs) in the glomerular basement membrane (GBM). Agrin is the predominant GBM-HSPG, but evidence that it contributes to the charge barrier is lacking, because newborn agrin-deficient mice die from neuromuscular defects. To study agrin in adult kidney, a new conditional allele was used to generate podocyte-specific knockouts. Mutants were viable and displayed no renal histopathology up to 9 months of age. Perlecan, a HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 63 publications
7
127
0
1
Order By: Relevance
“…Heparanase transgenic mice with complete loss of glomerular heparan sulphate only developed very mild albuminuria [11]. Furthermore, podocyte-specific agrin knockout mice [36] and podocytespecific exostosis-1 (EXT1) knockout mice [37] have been generated, both of which lack heparan sulphate in the GBM. Despite the absence of heparan sulphate, these mice do not develop proteinuria [36] either under normal conditions or when they are overloaded with albumin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparanase transgenic mice with complete loss of glomerular heparan sulphate only developed very mild albuminuria [11]. Furthermore, podocyte-specific agrin knockout mice [36] and podocytespecific exostosis-1 (EXT1) knockout mice [37] have been generated, both of which lack heparan sulphate in the GBM. Despite the absence of heparan sulphate, these mice do not develop proteinuria [36] either under normal conditions or when they are overloaded with albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, podocyte-specific agrin knockout mice [36] and podocytespecific exostosis-1 (EXT1) knockout mice [37] have been generated, both of which lack heparan sulphate in the GBM. Despite the absence of heparan sulphate, these mice do not develop proteinuria [36] either under normal conditions or when they are overloaded with albumin. While these recent data suggest that loss of heparan sulphate in the GBM alone does not lead to proteinuria, it is not clear whether loss of heparan sulphate under pathological conditions such as diabetic nephropathy accelerates or worsens proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Agrn Agrin Null allele: embryonic lethal; reduced number, size, and density of postsynaptic acetylcholine receptor aggregates in muscles; abnormal intramuscular nerve branching and presynaptic differentiation (Gautam et al 1996(Gautam et al ,1999; smaller brains (Serpinskaya et al 1999); abnormal development of interneuronal synapses (Gingras et al 2007); increased resistance to excitotoxic injury (Hilgenberg et al 2002); reduced number of cortical presynaptic and postsynaptic specializations (Ksiazek et al 2007). Floxed allele: Inactivation in podocytes does not affect glomerular charge selectivity or glomerular architecture (Harvey et al 2007).…”
Section: Prg1mentioning
confidence: 99%
“…The polyanionic heparan sulfate chains have been thought to be responsible for the charge-sieving properties of the glomerulus in which acidic macromolecules are preferentially excluded from urine (Groggel et al 1987;Groggel et al 1988). However, recent genetic evidence in which the principal GBM HSPG agrin was selectively knocked out in mouse podocytes revealed that reduction of GBM heparan sulfates did not alter chargeselectivity (Harvey et al 2007). One possibility is that the glycocalyx of either the endothelium or podocytes is responsible for charge-sieving.…”
Section: Glomerular Development and Filtrationmentioning
confidence: 99%